Penggunaan Silica Fume Sebagai Pengganti Sebagian Semen Dengan Penambahan Serat Spanduk Plastik (Banner) Terhadap Kuat Tekan Dan Kuat Tarik Belah Beton - Dawita Rama; Syahrul Syahriman; Savitri Prasandi Mulyani (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Concrete is a material that in general is the public's need for construction infrastructure facilities which is increasing along with the times, therefore choosing concrete as the main raw material for building construction is very important. Several things need to be reviewed when making... There is a lot of waste in the environment around us which can damage the environment around us, such as banner fiber, so we can process this banner fiber as an additional material in making concrete which can be used in the concrete making process. which can increase the compressive strength value of concrete and also save costs in the concrete manufacturing process. This research aims to obtain the effect of banner fiber as an additional material in making concrete accompanied by the addition of 10% silica fume. The mixing method is carried out by replacing cement with 10% silica fume with the addition of 2%, 4%, 65 and 8% banner fiber. The results of this research show that the use of banner fiber affects the compressive and tensile strength of concrete. The maximum values for compressive strength and tensile strength of concrete were obtained using a variation of 2% banner fiber with the addition of 10% silica fume, namely a compressive strength of 25.29 Mpa and a tensile strength of 2.0 Mpa.